Dynamic Simulation of a DC Microgrid for a Remote Community in Ghana - Atinkum, Godfred; Iqbal, M. Tariq; Quaicoe, John E. (Journal of Electronics and Electrical Engineering, 2025)
Microgrids are a growing solution for providing sustainable energy to remote communities. However, the complex mix of different sources requires careful analysis of their behavior over time. This paper presents dynamic modeling and simulation of a DC microgrid for a remote Ghanaian community. The system integrates a photovoltaic system, a wind generation system, a diesel generator, power converters, and a battery energy storage system, all of which are connected to a common DC bus. Component selection and system sizing were performed in Homer Pro. A detailed component-level model of the system is developed using MATLAB/Simulink to capture its transient behavior. Two maximum power point tracking techniques are used to optimize power extraction from the PV and wind generation systems, respectively. Simulated results include the responses observed for the components' voltage, current, and power waveforms under varying solar irradiation, wind, and changing load conditions. The dynamic simulations demonstrate effective voltage regulation, load adaptability, and system stability in response to changes in solar irradiance, wind speeds, and load changes.